2019
DOI: 10.1038/s41396-018-0338-z
|View full text |Cite
|
Sign up to set email alerts
|

Reductive metabolism of the important atmospheric gas isoprene by homoacetogens

Abstract: Isoprene is the most abundant biogenic volatile organic compound (BVOC) in the Earth’s atmosphere and plays important roles in atmospheric chemistry. Despite this, little is known about microbiological processes serving as a terrestrial sink for isoprene. While aerobic isoprene degrading bacteria have been identified, there are no known anaerobic, isoprene-metabolizing organisms. In this study an H 2 -consuming homoacetogenic enrichment was shown to utilize 1.6 μmoles isoprene h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(63 citation statements)
references
References 78 publications
1
62
0
Order By: Relevance
“…There is evidence of the enrichment of particular taxa when soils are subjected to atmospherically relevant concentrations of isoprene [39,87], and the cultivation of such bacteria might allow potentially different catabolic pathways to be discovered, and thus broaden the base from which primers/probes can be refined or new ones designed. In addition, there is a culture of a homoacetogen that can use isoprene as an electron acceptor [63], and there may well be more anaerobes that can metabolise isoprene that have evaded cultivation. Undoubtedly, such anaerobes would have catabolic pathways that are different from aerobes and potentially distinct from, e.g., alkene-oxidising anaerobes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence of the enrichment of particular taxa when soils are subjected to atmospherically relevant concentrations of isoprene [39,87], and the cultivation of such bacteria might allow potentially different catabolic pathways to be discovered, and thus broaden the base from which primers/probes can be refined or new ones designed. In addition, there is a culture of a homoacetogen that can use isoprene as an electron acceptor [63], and there may well be more anaerobes that can metabolise isoprene that have evaded cultivation. Undoubtedly, such anaerobes would have catabolic pathways that are different from aerobes and potentially distinct from, e.g., alkene-oxidising anaerobes.…”
Section: Discussionmentioning
confidence: 99%
“…Details about the isoprene-degrading strains belonging to these genera are provided in [62]. Finally, to our knowledge, no anaerobic bacteria, archaea, or fungi have been reported to use isoprene as a sole carbon and energy source, although Kronen et al [63] have recently shown that strict anaerobes can use isoprene as an electron acceptor to support homoacetogenesis, and thus anaerobic degradation of isoprene also warrants further attention.…”
Section: Diversity Of Isoprene-degrading Bacteriamentioning
confidence: 99%
“…Finally, the potential lyase substrate 2-hydroxy-2-methylbut-3-enoyl-CoA could be formed which is likely cleaved to methyl vinyl ketone and formyl-CoA. Another substrate for the lyase may be formed by isoprene reduction to isoamylene (Kronen et al, 2019). The latter alkene could be processed analogous to isobutene and isoprene oxidation to 2-hydroxy-2-methylbutyryl-CoA, which is readily used as substrate by the lyase from strain DSM 45062.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, several other putative alcohol and aldehyde dehydrogenases are substantially induced on acetone, 2-HIBA or both substrates and might play a role in acetone degradation as well, for example, the Adh1related WP_018331648.1 ( Table 1). Among these enzymes are also alcohol dehydrogenases (WP_018332348.1 mainly induced on acetone at an abundance of about 4% and WP_018334013.1 on both substrates at values between 0.4 and 0.8%) that are predicted to use 4-nitroso-N,N-dimethylaniline as artificial and mycofactocin as endogenous cofactor, as has recently been elucidated for a related dehydrogenase involved in ethanol oxidation (Krishnamoorthy et al, 2019). Remarkably, among the most abundant proteins is also a putative catalase/peroxidase (WP_033414714.1 with an abundance between 1.6 and 4.2%) which is indicative of high stress by reactive oxygen species, possibly produced in the course of uncoupled MimABCD activity.…”
Section: Proteome Of Acetone-and 2-hiba-grown Cellsmentioning
confidence: 94%
“…The genus appears to have varied metabolic capabilities, including low-temperature growth [32], debromination of polybrominated diphenyl ethers (PBDEs) [33], hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX) degradation [34,35], electrode-mediated acetogenesis [36], enhanced iron corrosion [37], and isoprene degradation [38]. To provide a more robust genome dataset, we sequenced and manually curated the genomes of four Acetobacterium strains, including A. malicum and three psychrophilic strains (A.…”
Section: Introductionmentioning
confidence: 99%